Identification of Extracellular Actin As a Ligand for Triggering Receptor Expressed on Myeloid Cells-1 Signaling - Fu, Lei; Han, Li; Xie, Caiyun; Li, Wenke; Lin, Lan; Pan, Shan; Zhou, You; Li, Zhi; Jin, Meilin; Zhang, Anding (Frontiers in Immunology, 2017)
Triggering receptor expressed on myeloid cells-1 (TREM-1) is a potent amplifier of proinflammatory innate immune reactions, and it is an essential mediator of death in sepsis. However, the ligand for TREM-1 has not been fully identified. Previous research identified a natural ligand of TREM-1 distributed on platelets that contributed to the development of sepsis. However, the exact signal for TREM-1 recognization remains to be identified. Here, we identified actin as a TREM-1-interacting protein on platelets and found that recombinant actin could interact with recombinant TREM-1 extracellular domain directly. Furthermore, actin co-localized with TREM-1 on the surface of activated Mouse macrophage RAW264.7 cells interacting with platelets. Additionally, recombinant actin could enhance the inflammatory response of macrophages from wt mice but not from trem1-/- mice, and the enhancement could be inhibited by LP17 (a TREM-1 inhibitor) in a dose-dependent manner. Importantly, extracellular actin showed co-localization with TREM-1 in lung tissue sections from septic mice, which suggested that TREM-1 recognized actin during activation in sepsis. Therefore, the present study identified actin as a new ligand for TREM-1 signaling, and it also provided a link between both essential regulators of death in sepsis.